(untitled) (American Journal of Islam and Society, 2005)
This book belongs to the genre of studies attempting to extend and broaden Muslim channels of communication to “western” academic and intellectual circles in general, and to their American counterparts in particular. It starts from the conventional apologetic premise that Islam is misunderstood and, in many instances, mystified both by unrepresentative scholarly works on the one hand, and the dynamics of Muslim history and actions on the other. Marked differences between the historical, social, and political experiences of Muslims and Europeans, as reflected in different modes of organization and discourse, have put serious impediments in the way of mutual understanding across the cultural divide separating the two worlds. One reflection of such distrust is manifested in the indifference shown by American scholars and statesmen toward what Safi designates as “Islamic reformists” and their forward-looking agenda. Despite the latter’s ambitions to advance a pluralist and democratic society in consonance with the modern world, the former continue to dismiss such claims as both “opportunistic” and insincere. These perceptions, according to the author, are driven by a strong sense of skepticism about the commensurability of Islamic values with modern western ideals as well as by vested American geostrategic interests. Safi challenges such attitudes by emphasizing the importance and vital significance of Islamic reform, which he defines as the “middle ground and the moral synthesis between the nationalist-secularist and the moral- Islamist forces” at the heart of the unsettling tensions that inform sociopolitical transformations in the Arab and Islamic worlds (p. xii). Reform of this kind should be able to appropriate the universal elements of the historical Muslim experience in order to transcend the political and cultural institutions of classical and contemporary Muslim societies, and to bring about a creative synthesis of Islam and modernity (p. xi). Safi’s main contention ...